MANAJEMEN PERSEDIAAN BAHAN BAKU BERBASIS PADA PT. TUFFINDO NITTOKU AUTONEUM KARAWANG - Priyandanu, Hananda; Tabrani, Muhamad; Suhardi, Suhardi; Mutaqin, Zaenal (JURNAL ILMIAH M-PROGRESS, 2020)
In the current era of globalization, information technology is advancing rapidly. The computer which isequipment that was created to facilitate human work, when achieving progress both in making hardware andsoftware. PT. Tuffindo Nittoku Autoneum is in need of an information system that supports and provides fastand precise access to its business activities. For this reason the author tries to make a Raw MaterialInventory System which until now has not been computerized. At this time PT. Tuffindo Nittoku Autoneum has been well developed for the information system used, only for some parts such as the warehouse, theexisting system at PT. Tuffindo Nittoku Autoneum is still done manually, starting from recording the receiptof goods from suppliers, to storing other data relating to the inventory process to making reports, making itpossible during the process of error occurred in recording, inaccurate reports made and delays in finding thenecessary data. The design of this information system is the best solution to solve the problems that exist inthis company, as well as with a computerized system can achieve an effective and efficient activity insupporting the activities of this company. A computerized system is better than a manual system to run moreeffectively and efficiently and the new raw material warehousing system is more conducive than the previoussystem.Keywords: System Design, Raw Material Inventory Management